Achieving grain refinement and ultrahigh yield strength in laser aided additive manufacturing of Ti−6Al−4V alloy by trace Ni addition. Issue 4 (4th July 2021) - Sui, Shang; Chew, Youxiang; Weng, Fei; Tan, Chaolin; Du, Zhenglin; Bi, Guijun
ABSTRACT: Fabricating fine equiaxed grains without undesirable secondary phases is highly challenging for additively manufactured Ti−6Al−4V alloy. The reference amount of Ni addition, which can achieve grain refinement without secondary phase formation, is 0.9 wt. % based on Thermo-Calc calculation. The Ti−6Al−4V−0.9Ni alloy produced by laser-based directed energy deposition demonstrate refined microstructure and an ultrahigh yield strength (1309 MPa). A modified quantitative model is proposed to analyse the strengthening mechanism, and the results demonstrate that the yield strength increment is mainly ascribed to the refined α phase. This work can contribute to the development of customised titanium alloy using additive manufacturing.